Modified BEAM rubber agroforestry models: RRYIELD and RRECON - Grist, P.; Menz, K.; Thomas (Australian Centre for International Agricultural Research, 1998)
This paper details changes to the BEAM models, RRYIELD and RRECON, which are two of a series of bioeconomic models developed by the Bioeconomic Agroforestry Modelling (BEAM) project. The RRYIELD model deals with the biophysical components of a rubber-based agroforestry system. It focuses on the changes in output (latex, wood and intercropped annual and perennial crops) in response to a number of bioclimatic, topographic and silvicultural variables. Outputs are measured annually over the life of the plantation. The RRYEILD model is linked to an economic model RRECON used to determine the economic returns from a rubber plantation. The two models are used in combination as an extension and research tool to supply farmers or researchers with information on the viability of alternative rubber intercropping systems. The original model was developed for large estates and government plantations. The changes outlined in this report aimed to make the model more applicable to smallholders in Imperata infested areas of Southeast Asia, particularly Indonesia. These modifications were made progressively and were documented in a series of five papers. They are now presented here together in a single paper.